Konkurencyjność edukacyjna krajów Regionu Morza Bałtyckiego (RMB) - Kisiel-Łowczyc, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article deals with the problems connected with the educational competitiveness of countries from the Baltic Sea Region. These countries are facing a new phase of economical integration (new markets are opening and the production potential is growing). Regional co-operation of the Baltic Sea Region countries may become the factor which is going to increase the competitiveness of these economies. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 206-211